A novel approach towards a histone replacement system in Tetrapods - Maximilian Pfisterer; Amelie Pritz; Anna Parry; M. Lienhard Schmitz (PLoS ONE, 2026)
Histone replacement systems are valuable tools for studying histone modifications, but in vertebrates this is so far only possible by labor-intensive CRISPR base editing of each single histone gene. To facilitate such studies, we developed an alternative method and conducted proof-of-principle experiments using histone 2B (H2B) as an example. This method relies on shRNA targeted degradation of endogenous histone mRNA and simultaneous re-expression of a replacement histone. Due to their limited histone gene number, chicken cells proved suitable as a tetrapod model system for this approach. In the first-generation system we developed an shRNA design tool that identified shRNAs leading to efficient downregulation of each of the canonical histones using a single doxycycline (Dox)-inducible shRNA. As H2B knockdown cells are not viable, they were rescued by simultaneous Dox-inducible re-expression of H2B. Since the comparability between wild-type and mutated histone variants is limited due to random chromosomal integration, we developed a second-generation “inducible knockdown-re-expression” system. This new version employs genomic landing pads to facilitate Bxb1 recombinase-mediated cassette exchange with mutated histones. The system successfully rescued reconstituted cells from histone depletion-induced cell death, but requires optimization to align histone expression levels with endogenous levels. Overall, this system offers a promising new method for studying specific histone modifications in chicken cells.